Developing Dissertation Support in the Writing Centre - O'Regan, Keith (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2022)
The uneven levels of writing support that dissertation writers receive throughout each stage of their PhDs has contributed to low completion rates and general dissatisfaction with the doctoral process. By offering both collective and individual assistance, the Café and one-to-one writing programming described herein centres students in their own work by examining the often-unspoken expectations that structure their PhDs. This programming establishes honest communication with dissertation writers in order to promote self-advocacy and intrinsic motivation so that they may take greater control over their projects. By modeling a reflective understanding of dissertation writing, this programming enhances longer term productive processes that enable higher completion rates and a greater sense of fulfillment with the PhD.